Elastic Language : How and Why we Stretch our Words - Zhang, Grace Q. (Cambridge : Cambridge University Press, 2015)
Elastic language carries non-specific and stretchable meaning, as in'He loves her, kind of'. It is used like a slingshot, targeting various strategic goals. Consolidating current research and charting new directions, this book develops a refreshing theory of elasticity, empirically attested by natural language data from tension-prone encounters between Australian Customs officers and passengers. The theory proposes three principles (fluidity, stretchability and strategy) and offers a systematic look at how elastic language, as a sliding scale, works to balance strengthening and weakening speech tones, to firm and soften a speaker's stance, and to reveal and evade the truth. The comparative analysis of forms, functions, and context confirms that elastic language is fluid, stretchable, and strategic. It serves both cooperative and competitive functions, and social and speech factors impact on its use. This book will appeal to students and researchers working in pragmatics, applied linguistics, sociolinguistics, discourse analysis, and communication.
Title from publisher's bibliographic system (viewed on 07 Mar 2017).
Keywords: Semantics; Plays on words; Vagueness (Philosophy); Speech acts (Linguistics)